Pregnancy Outcome in Gestational Diabetes Mellitus - Bajracharya, Anu; Saha, Rachana; Shakya, Archana (Journal of Kathmandu Medical College, 2015)
Background: Gestational diabetes mellitus is a metabolic disorder defined as glucose intolerance with the onset or fi rst recognition during pregnancy. Gestational diabetes mellitus is associated with higher incidence of maternal diabetes mellitus later in life. It poses a risk to the pregnant woman and to the fetus. Hence, it is imperative for an early detection and management of the disease to ensure better maternal and foetal outcomes. Objective: To assess the prevalence of gestational diabetes mellitus and to analyze the maternal and perinatal outcomes of gestational diabetes mellitus patients who delivered in the hospital during the study period. Methods: A hospital based descriptive observational study was conducted at Kathmandu Medical College Teaching Hospital for a period of one year from 1st January 2013 to 31st December 2013. All the cases of gestational diabetes mellitus were included in the study. Patients were followed from the time of admission to the time of discharge after delivery. Pertinent information obtained were demography, gestational age at diagnosis and delivery, pregnancy complications, intervention and perinatal morbidity and mortality. Results: Out of 2845 deliveries, 45 patients were diagnosed as gestational diabetes mellitus and admitted during the period of study. The prevalence of gestational diabetes mellitus was 1.58% in this hospital. The most common maternal and neonatal complications were gestational hypertension (20%), hypoglycemia (8.89%) and macrosomia (8.89%) respectively. Conclusion: This study is important in providing information about the maternal and neonatal outcomes of gestational diabetes. By proper monitoring and good glycaemic control during the antenatal period, the adverse maternal and neonatal complications of gestational diabetes mellitus can also be reduced. DOI: http://dx.doi.org/10.3126/jkmc.v3i3.12246 Journal of Kathmandu Medical College Vol. 3, No. 3, Issue 9, Jul.-Sep., 2014, Page: 107-112